Surface Rendering of External Genitalia of a Fetus at the 32nd Week of Gestation Affected by Partial Androgen Insensitivity Syndrome - Vincenzo Mazza; Emma Bertucci; Silvia Latella; Carlotta Cani; Pierluca Ceccarelli; Lorenzo Iughetti; Fulvia Baldinotti; Antonio Percesepe (Hindawi Limited, 2013)
Objectives. To demonstrate the feasibility of the prenatal diagnosis of partial androgen insensitivity syndrome by 3D-4D ultrasound. Methods. To report prenatal diagnosis of partial androgen insensitivity syndrome at 32nd week of gestation by 3D-4D ultrasound in a fetus with a 46XY karyotype, testing negative to the mutation analysis of SRY gene and the 5α-reductase 2 gene (SRD5A2). Results. 3D-4D surface rendering allows the detection of external and internal genital malformations and can address the prenatal diagnosis of PAIS and can exclude associated complications. Conclusions. Prenatal diagnosis of PAIS allows an adequate parental counseling and an early optimal management of the condition, not only for the psychological and social reflections but also for the avoidance of complications and postnatal morbidity due to misdiagnosis or delays in the treatment of the genital ambiguity.